Wellbeing frameworks for the Treasury - Anita King; Gulnara Huseynli; Nairn MacGibbon (New Zealand Government, The Treasury, 2018)
Over recent years, the Treasury has increasingly focussed on using a living standards framework to assess the impact of government policies on the wellbeing of New Zealanders. The purpose of this report is to evaluate a range of different frameworks for measuring current wellbeing that exist both internationally and domestically as part of the further development of the Treasury Living Standards Framework.
Keywords: 330